PENGARUH WISATA EDUKASI, NIAT PERILAKU, DAN LOKASI TERHADAP NIAT BERKUNJUNG ULANG KE TAMAN ISMAIL MARZUKI JAKARTA - Leni Anggraini; Suryani Chodidjah (Human Capital Development, 2023)
This study aims to determine the effect of educational tourism, behavioral intention and location on the intention to return to Taman Ismail Marzuki Jakarta. The population involved in this study were tourists at Taman Ismail Marzuki using the accidental sampling method with a total of 100 respondents. This study used data analysis using quantitative methods assisted by SPSS version 26 software. The results showed that the educational tourism variable had a positive and significant influence on intention to return. Behavioral intention has a positive and significant influence on intention to revisit. Location has a positive and significant influence on the intention to revisit. Simultaneously, educational tourism, behavioral intention, and location influence intention to revisit by 66.4% while the remaining 33.3% is influenced by other factors not included in this study.